Transformation of biomass : theory to practice - Hornung, Andreas (Chichester, West Sussex : Wiley, 2014)
'Biomass is a key resource for meeting the energy and material demands of mankind in the future. As a result, businesses and technologies are developing around biomass processing and its applications.Transformation of Biomass: Theory to Practice explores the modern applications of biomass and bio-based residues for the generation of energy, heat and chemical products. The first chapter presents readers with a broad overview of biomass and its composition, conversion routes and products. The following chapters deal with specific technologies, including anaerobic digestion, pyrolysis and gasification, as well as hydrothermal and supercritical conversion. Each chapter details current practises, recent developments, business case models and comprehensive analysis of the problems associated with each approach, and how to optimize them.Topics covered include: Anaerobic digestion Reactor design Pyrolysis Catalysis in biomass transformation Engines for combined heat and power Influence of feedstocks on performance and products Bio-hydrogen from biomass Analysis of bio-oils Numerical simulation and formal kinetic parameters evaluation Business case development This textbook will provide students, researchers and industry professionals with a practical and accessible guide to the essential skills required to advance in the field of bioenergy'--
'Transformation of Biomass: Theory to Practice explores the modern applications of biomass and bio-based residues for the generation of energy, heat and chemical products'--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Biomass chemicals; Biomass; SCIENCE / Chemistry / General; Biomass; Biomass chemicals; Electronic books; Electronic books